IT enabled services: growing form of telework - Ramani, S. (2000)
IT enabled services, that is, electronic commerce activity carried out at a distance from the front office where customer contact and sales are carried out, are growing rapidly in India. What is the nature of services offered? What is the growth potential in this area? - Reproduced
Keywords: Information technology - India; Electronic commerce